Sustainable Energy Self-sufficiency - Obrecht, Matevž; Fale, Martin (Mastering Sustainability in Supply Chains, 2026)
Energy self-sufficiency means that we are capable of generating enough electrical energy on a micro-level to power all systems that require electricity to operate. Solar power can be used to generate electrical energy. Through these devices, we convert solar energy into electrical energy. If we cannot store the excess electricity produced, we feed it back into the electrical grid. Since solar power plants cannot provide continuous production, we either need to store excess electrical energy or obtain the missing energy from the electrical grid. For storage, we require energy storage systems, such as batteries. A battery pack from electric vehicles can also be used as an energy storage system. By managing these storage systems, we can regulate the daily demand for electrical energy on a micro-level. Through an energy marketplace, we can trade electricity and manage the generated electrical energy of the micro-location. Combining a solar power plant with a heat pump on a micro-level can create a fully self-sufficient energy system for the micro-location, capable of operating independently of the electrical grid.